Political Order and Political Decay : From the Industrial Revolution to the Globalization of Democracy - Fukuyama, Francis (New York Farrar, 2015)
The second volume in a landmark chronicle of the modern state examines how societies develop strong, impersonal, and accountable political institutions, discussing such topics as the French Revolution, the Arab Spring, and contemporary American politics.
Include Index and Bibliography
Keywords: Order -- Comparative government -- Democracy